Pengadaan Penanaman Tanaman Kumis Kucing Sebagai Obat Keluarga di Setiap Halaman Rumah Warga Serta Pelatihan Cara Mengolah Tanaman Kumis Kucing Menjadi Minuman Obat di Desa Berancah, Kecamatan Bantan, Kabupaten Bengkalis - Zulkarnaini Zulkarnaini; Suyanto Suyanto; Miftah Azrin (CANANG: Jurnal Pengabdian Masyarakat, 2024)
Kumis Kucing (Orthosiphon aristatus) is an herb that can be considered special in traditional medicine. All parts of it, from roots to flowers, are believed to have medicinal effects and strengthen performance. Community service has been carried out with the aim of increasing knowledge and understanding and teaching utilization to people who have empty gardens in Berancah Village in the management of Kumis Kucing (Orthosiphon aristatus) as family medicine. This community service activity was carried out to the Berancah Village community in the Village Hall by Field Supervisors and assisted by Kukerta students. The method in this implementation is carried out in 4 (four) stages, namely Socialization, Competency building, Activity implementation, and Monitoring and Evaluation